Boosting Students' Vocabulary through Index Card - Soviyah, Soviyah; Akhsan, Nur Rifai (Journal of English and Education (JEE), 2008)
There are thousands of words in English. Learning these words is a big problem for students of English. However, there are ways to solve this problem. One way is to become familiar with the process of word formation. This process enables students to understand how a word is formed. This analysis is in important and useful to learn because they are very commonly used in English. Developing some skills in taking words apart will help students better understand what they read, what the meaning ofa word, and finally increase students' vocabulary.One way to learn word formation is through index card games. These games will help students learn how a word is constructed in various ways, and even stimulate them to initiate making new word or sentences using their own interest.The writers have conducted action research to use the index card to improve the student's vocabulary. To get more successful achievement, the writes limit to teach suffixes only, namely Verb suffixes. Noun suffixes. Adjective suffixes and Adverb suffixes. For one semester, the writers teach suffixes using index cards in different models, such as Match it, Challenge it. Winsor Loses.The result shows that students may improve their vocabulary mastery (70%), uphold students' motivation (60%), build confidences to speak (40%),generate classroom energy (30%), recognize word formation process (70%), participate in class discussion (25%), and & get better class attendance. From the result above, the-writers believe index card is very useful to improve students' vocabulary, particularly in word formation.